Development of a Proximity-Based Pet Adoption Website Application - Muhamad Akbar Susanto; Pratyaksa Ocsa Nugraha Saian (International Journal Software Engineering and Computer Science (IJSECS), 2025)
This study examines the development of a web-based application designed to facilitate pet adoption through practical, structured, and location-based mechanisms. The primary problem addressed is the absence of digital platforms capable of integrating adoption processes more efficiently than traditional methods. The application employs Java Spring Boot for backend architecture, ReactJS for frontend interface, and MongoDB for data management. The Haversine formula with a 50 km radius was implemented to display animals based on proximity to users. Algorithm implementation results demonstrate that Haversine effectively calculates distances and presents animals according to nearest locations, thereby enhancing search accuracy and relevance for prospective adopters. Core functionality includes a WebSocket-based real-time chat system enabling direct communication between prospective adopters and owners without page reloading. System development followed the Waterfall model encompassing requirements analysis, design, implementation, and testing phases. Evaluation through User Acceptance Testing (UAT) using a 1-4 Likert scale yielded satisfaction rates of 82% among prospective adopters and 84.5% among pet owners, both categorized as "highly satisfied." These findings validate that the application serves as a more efficient and structured alternative, with potential for further development to support expanding user bases in the future.